Efficacy Evaluation of Iclaprim in a Neutropenic Rat Lung Infection Model with Methicillin-Resistant Staphylococcus aureus Entrapped in Alginate Microspheres. (4th October 2017) - Huang, David; Hawser, Stephen; Morrissey, Ian; Murphy, Timothy
Abstract: Background: The objective of this study was to demonstrate the effect of iclaprim, a new generation diaminopyrimidine, in a neutropenic rat lung infection model with methicillin resistant Staphylococcus aureus (MRSA). Methods: S. aureus strain AH1252, a thymidine knockout of the MRSA wild type AW6 strain, was utilized for this study. The bacterial strain was diluted in a 2% alginate buffer, which was added dropwise in a ratio of 1:5 into 50 mM MgCl to form alginate beads. The alginate beads reduce the efficacy of bacterial clearance similar to that seen in the cystic fibrosis population. A 5.25 × 10 4 bacterial inoculum was administered intratracheally to groups of 9 rats with prepared alginate bacteria suspensions, under isoflurane anesthesia. Beginning 2 hours post infection, rats received either iclaprim or vancomycin for 3 days via subcutaneous injection every 12 hours. Twelve hours after the last treatment, rats were euthanized and lungs collected for CFU determination. Results: The Table below shows survival, CFU/gram of lung, and change in CFUs (Standard Error of the Mean (S.E.M.) from baseline by treatment or vehicle group. Conclusion: In this rat lung infection model increased survival was observed in both iclaprim and vancomycin treatment groups, compared with the infection controls. Rats receiving iclaprim demonstrated a 5.34 log10 CFU reduction from the 72 hour infection whereas vancomycin-treated rats showed a 3.38 log10 CFU reduction from the 72 hour infection controls.#8232;Based on these data, further evaluation of iclaprim for S. aureus lung infections among the cystic fibrosis population is warranted. Disclosures: D. Huang, Motif Bio: Employee, Salary